STORAGE OF TREMA (Trema orientalis Linn. Blume) SEEDLINGS IN NURSERIES AND THEIR EFFECT ON GROWTH - deddy dwi nur cahyono; Dida Syamsuwida; Naning Yuniarti; Aam Aminah; NFN Danu; Kresno Agus Hendarto; Dharmawati F Djam'an; Nurma Wati Siregar (Jurnal Perbenihan Tanaman Hutan, 2021)
Trema (Trema orientalis Linn. Blume) is one of forest tree species that has potency to be used as a renewable biomassa energy source. The successful of the development of this species is strongly depent on the quality and quantity of the seedlings. The problems often occur when the seedlings should be stacked up in a nursery due to the unreadiness of the planting sites and rainy season. Therefore, the seedlings should be stored and managed by suppressing their growth during storage. The aim of the study is to examine the growth responses of trema seedlings to the treatments of growth retardants and shade during storage in the nursery and replanting in the field. Slow growth method was used in this study by applying growth inhibitors (250 ppm paclobutrazol, 0.5% NaCl) and regulating shade conditions (90% shade, 50% shade and no shade) and stored for 6 months. After storing in the nursery, treated seedlings were replanted in the field and observing for their growth for 17 months. The results showed that the growth of the seedlings could be suppressed for 6 months by applying 250 ppm paclobutrazol under 50% shade condition (T=32.2˚C; RH=62%, light intensity of 27,300 flux). This condition suppressed the growth of the diameter and root shoot ratio by an average of 49% and 11% respectively, and maintain the seedling survival up to 97.67%. The best growth in height and diameter in the field was achieved by a combination of treatment using NaCl with a shade intensity of 50%. It is concluded that the effectiveness of  the application of inhibitors on trema seedlings when were stored in the nursery was different from that used to increase the growth of trema in the field.